1980
DOI: 10.1901/jaba.1980.13-571
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Police Vehicle Accidents Through Mechanically Aided Supervision

Abstract: Tachograph recorders were installed in 224 vehicles of a metropolitan police department to monitor vehicle operation in an attempt to reduce the rate of accidents. Police sergeants reviewed each tachograph chart and provided feedback to officers regarding their driving performance. Reliability checks and additional feedback procedures were implemented so that upper level supervisors monitored and controlled the performance of field sergeants. The tachograph intervention and components of the feedback system ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Examples can be seen with: improving speed estimation [13,14], increasing compliance with traffic laws [15], reducing police vehicle accidents [16], reducing speeding [17], increasing seat belt usage [18], improving car following distance [19], and improving situation awareness [20,21].…”
Section: Feedbackmentioning
confidence: 99%
“…Examples can be seen with: improving speed estimation [13,14], increasing compliance with traffic laws [15], reducing police vehicle accidents [16], reducing speeding [17], increasing seat belt usage [18], improving car following distance [19], and improving situation awareness [20,21].…”
Section: Feedbackmentioning
confidence: 99%
“…Similarly, a number of studies have demonstrated the benefits of using individual feedback to increase safety-related behavior. Vehicle crashes among police patrollers decreased significantly when individual behavioral feedback was available from in-vehicle tachograph recorders (Larson et al, 1980). Individual feedback techniques were also effective at increasing safe work practices in a coal mine (Rhoton, 1980), among nurses (Babcock, Sulzer-Azaroff, Sanderson, & Scibak, 1992;DeVries, Burnette, & Redmon, 1991), and among the staff in a group home (Alavosius & Sulzer-Azaroff, 1986).…”
Section: Applications Of Feedback To Improve Occupational Safetymentioning
confidence: 99%
“…For example, on one problem highway speeding was reduced an average 13 percent by special signs showing the percentage of drivers who kept within the speed limit that week on that stretch of highway (Van Houten et al, 1980). Another study found a similar reduction in speeding on two separate highways, with an average 42 percent reduction in accidents on the highway and an average 39 percent reduction in vehicle damage costs for accidents that did occur (Van Houten & Nau, 1981; see also Larson et al, 1980). Although this and similar studies are not commonly considered "therapy" research, they add considerably to the impact that psychological techniques can have on the health and well-being of the American people.…”
Section: Preventing Accidents and Violencementioning
confidence: 94%